Keterlibatan Karyawan dalam Pencapaian Tujuan Strategis: Employee Involvement in Achieving Strategic Goals - Sugeng Sukoco; Fahmi Win Iranto (LITERA: Jurnal Ilmiah Mutidisiplin, 2025)
The achievement of strategic organizational goals strongly depends on active employee engagement in the planning, execution, and evaluation of strategies. This article aims to conceptually examine the role of employee involvement in achieving organizational strategy, complemented by secondary data analysis to provide empirical support. The study adopts a descriptive-qualitative approach by reviewing academic literature and survey data related to employee engagement and organizational performance. The results show that high employee engagement correlates positively with the achievement of strategic objectives, especially in productivity, innovation, and employee retention. The article recommends improving internal communication, strategic training, and employee participation in decision-making processes as effective measures to enhance engagement.